A twist at infinite distance in the CHL string - Veronica Collazuol; Ilarion V. Melnikov (Journal of High Energy Physics)
Abstract We analyze a space-time algebra of BPS states that emerges in the infinite distance limit in the moduli space of the nine-dimensional CHL string as the theory decompactifies to the ten-dimensional E8 × E8 heterotic string. We find an affine algebra as expected from the heterotic case, but in a twisted version.